2019
DOI: 10.3390/ijerph17010101
|View full text |Cite
|
Sign up to set email alerts
|

Childcare Center Characteristics Moderate the Effects of a Physical Activity Intervention

Abstract: Center-based early childhood education and care (ECEC) programs are well-positioned to create positive impacts on the health and development of large numbers of young children by promoting physical activity using evidence-based programs. Studies testing physical activity programs for young children should examine the circumstances under which programs are most effective by assessing the role of contextual factors on program outcomes. The purpose of this study was to examine the moderating effects of baseline E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Eleven studies (12 articles) related the size of the outdoor play area to children's PA and ST. Of the 11 studies, nine were cross-sectional studies, one was a controlled before-after study [27] and one was a randomised controlled trial [59]. Five studies were conducted in Australia [20,27,[60][61][62], three in the USA [26,54,59] and one in Denmark [56]. One study, reported in two articles, was conducted in both the USA and Sweden [16,63].…”
Section: Absolute Size Of the Outdoor Play Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies (12 articles) related the size of the outdoor play area to children's PA and ST. Of the 11 studies, nine were cross-sectional studies, one was a controlled before-after study [27] and one was a randomised controlled trial [59]. Five studies were conducted in Australia [20,27,[60][61][62], three in the USA [26,54,59] and one in Denmark [56]. One study, reported in two articles, was conducted in both the USA and Sweden [16,63].…”
Section: Absolute Size Of the Outdoor Play Areamentioning
confidence: 99%
“…Two studies used smaller sizes of outdoor play areas as reference thresholds for comparison: ≤200m 2 versus 900m 2 and > 2700 m 2 [64], and < 386 m 2 versus ≥386m 2 [26]. Another three studies defined larger playground sizes for comparison: <505m 2 versus ≥505m 2 [54], < 1038 m 2 versus ≥1038m 2 [59], and < 1200 m 2 versus 3000m 2 and ≥ 3000 m 2 [16,63]. Olesen et al measured the size of accessible playground area across ECECs and used them as continuous variables ranging from 567m 2 to 5175 m 2 [56].…”
Section: Absolute Size Of the Outdoor Play Areamentioning
confidence: 99%
See 1 more Smart Citation
“…CPARG study designs, intervention designs, partnerships with stakeholders, measurement, analyses, implementation strategies, and implementation monitoring grew in sophistication over time as we learned from experience. Investigators should plan from the beginning to facilitate and measure sustainability of change, as in LEAP [ 92 , 96 ] and to conduct dissemination and translation research in order to get effective interventions out in the “real world,” as in SHAPES [ 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%